2004
DOI: 10.1029/2004gl020321
|View full text |Cite
|
Sign up to set email alerts
|

Distant magnetotail reconnection and the coupling to the near‐Earth plasma sheet: Wind and Geotail case study

Abstract: We have studied the coupling between the distant and near‐Earth plasma sheet during an 8 hour interval on April 1, 1999 when the interplanetary magnetic field was northward and dominated by the By component. During these 8 hours the Geotail spacecraft sampled the near‐Earth magnetotail at XGSM ∼ −25 RE while the Wind spacecraft was located in the distant magnetotail at XGSM ∼ −60 RE. Wind detected long duration (>8 hours) and likely spatially extended convective high speed flows indicative of continuous magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…From WIND data, Øieroset et al. (2000, 2004) reported five fast flow events occurring in the tail about 25–60 RE during a four‐day period with mainly northward IMF conditions. The analysis of these fast flows suggests that quasi steady reconnection can occur in the mid‐magnetotail region during periods of persistent northward IMF.…”
Section: Discussionmentioning
confidence: 99%
“…From WIND data, Øieroset et al. (2000, 2004) reported five fast flow events occurring in the tail about 25–60 RE during a four‐day period with mainly northward IMF conditions. The analysis of these fast flows suggests that quasi steady reconnection can occur in the mid‐magnetotail region during periods of persistent northward IMF.…”
Section: Discussionmentioning
confidence: 99%
“…The dawn‐dusk spatial localization of PSBL beamlets then seems to be very natural because as it was reported by Angelopoulos et al [1989], bursty bulk flows (BBFs), which are also the result of magnetotail reconnection and which may be considered as the CPS counterparts of PSBL beamlets, have a finite spatial extent (∼1–3 R E [ Sergeev et al , 1996; Angelopoulos et al , 1997; Kauristie et al , 2000; Nakamura et al , 2001, 2004a]). Recently, Oieroset et al [2004] provided experimental evidences that energization processes could have rather large duration (∼10 hours) and finite spread in dawn‐dusk direction (≥1 R E ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that the asymptotic asymmetric conditions and the guide field are the two main factors determining Hall field patterns (Oieroset et al 2004;Cassak & Shay 2007;Cassak & Shay 2008;Mozer et al 2008;Pritchett 2008;Eastwood et al 2010). The asymptotic asymmetry and the guide field for the three events are listed in Table 1.…”
Section: Analyses and Discussionmentioning
confidence: 99%
“…The asymptotic asymmetry parameter (Phan & Paschmann 1996) is found to play an important role in determining the magnetic field and electric field pattern in the Hall effect (Oieroset et al 2004;Cassak & Shay 2007;Mozer et al 2008). In previous studies, the asymmetry is typically estimated using asymptotic (also called background) plasma parameters in the inflow regions of reconnection.…”
Section: Introductionmentioning
confidence: 99%